Keharmonisan Keluarga, Konformitas Teman Sebaya dan Kenakalan Remaja - ., Winarsih; Saragih, Sahat (Persona:Jurnal Psikologi Indonesia, 2016)
This study aims to determine the relationship between family harmony andconformity peers in juvenile delinquency SMK "X" in Surabaya. The method in this studyusing a quantitative approach. Subjects were taken by random sampling technique ofdata collection tools used is the scale delinquency, harmony scale, and the scale ofconformity. Anaisa data using multiple regression analysis. The results of calculationsusing multiple regression analysis showed at t = -4.354, p = 0.000, meaning that therewas a significant negative correlation between family harmony with juvenile delinquency.The higher the level of family harmony, then the lower the rate of juvenile delinquency.From the results of partial analysis shows that t = -0.170 at p = 0.030 (p> 0.01),meaning there is no correlation between peer conformity with juvenile delinquency. Theresults of multiple regression analysis showed the value of F = 11.551, p = 0.000, whichmeans that there is a significant relationship between family harmony and conformitypeer to juvenile delinquency. Family harmony and conformity to peer can be a predictorof the level of juvenile delinquency with R2 = 0.160. This means that effective sumnganjuvenile delinquency and peer conformity to juvenile delinquency by 16%, students 84%are influenced by other factors.Keywords : juvenile delinquency, family harmony, conformity peers